CuAAC click chemistry: a versatile approach towards PVDF-based block copolymers. Issue 27 (28th June 2018) - Terzic, I.; Meereboer, N. L.; Loos, K.
Abstract : Functionalized benzoyl peroxide-initiated polymerization of vinylidene fluoride allows straightforward preparation of PVDF-based block copolymers with an appealing crystallization behavior. Abstract : Alkyne/azide end terminated PVDF homopolymers were synthesized via free-radical polymerization using functional benzoyl peroxides as initiators. This approach allows the preparation of PVDF triblock copolymers with various functional blocks (polystyrene, poly( N -isopropylacrylamide) and poly( tert -butyl acrylate)) and tunable crystallization behavior using copper(i )-catalyzed azide–alkyne cyclo-addition.